EFEKTIVITAS UNDANG-UNDANG NOMOR 2 TAHUN 2002 TENTANG KEPOLISIAN BAGI ANGGOTA YANG MELAKUKAN DUGAAN PELANGGARAN ATAUPUN TINDAK PIDANA - I Komang Gede Nuarsa; A.A. Sagung Poetri Paraniti; Ida Bagus Anggapurana Pidada (Bajang Institute, 2023)
The problems in this research are How effective is Law Number 2 of 2002 concerning the police for members who commit alleged violations or criminal acts and What are the obstacles in the implementation of Law Number 2 of 2002 concerning the police for members who commit alleged violations or criminal acts. What are the obstacles in the implementation of Law Number 2 of 2002 concerning the police for members who commit alleged violations or criminal acts. The conclusion of this study is to find several violations or crimes that have been committed by the Indonesian police, including: Crime of Narcotics Abuse, Crime of Theft, and Violations of Discipline. The Effectiveness of Law Number 2 of 2002 Concerning the Indonesian National Police In the case of premeditated murder involving Ferdy Sambo, et al. help describe the parts that were violated such as Article 35 (1), Article 30 (1), Article 19 (1), and Article 23. General factors that influence the law enforcement process: Legal Factors, Law Enforcement Factors, Facility Factors or Supporting Facilities, Community Factors, and Cultural Factors